An equivalence based classification of [6, 3, 4] error correcting codes over GF(5). (4th July 2022) - Sultana, Sharmin; Akter, Hasina; Dey, Partha Pratim
Abstract: We were able to classify all 1-error correcting [5, 3] codes over GF (5) in paper [1] and [5, 2] ternary codes in paper [2]. Now, our focus is an equivalence based classification of error correcting linear codes of length 6 over GF (5). In paper [3], we investigated the equivalence of [6, 3, 4] codes of length 6 and dimension 3 over GF (4). In this paper we classify the [6, 3, 4] codes over GF (5). We explore the weight distribution of these codes as well as their duals.